Implementasi Teori Permainan Dalam Penentuan Strategi Pemasaran Produk Bakso ( Studi Kasus : Warung Bakso di Kabupaten Bombana ) - Sitti Fatmah Nuraini; Asrul Sani; Muh. Kabil Djafar; La Ode Sabran (JOSTECH Journal of Science and Technology, 2023)
This research aims to determine the right marketing strategy for meatball products and generate optimum profits using Game Theory. The novelty of the research is lies in the object study. The data used in this study is primary data collected by using a questionnaire given to visitors at three Bakso Warungs in Bombana Regency, namely Warung Bakso Solo, Baper, and BRI. The number of samples to be observed is 50 respondents. Then the data that has been collected will be tested for validity and reliability, and then will be processed using the Game Theory method. Based on the results of the analysis obtained the optimal strategy for each meatball stall. The optimal game value obtained shows that the advantage of Warung Bakso Solo in marketing is that product prices are cheaper, but Warung Bakso Solo must use a strategy to improve the cleanliness of the stalls so that sales are optimal. The advantage of Warung Bakso Baper in marketing is the politeness of employees, but Warung Bakso Baper must improve in the strategy of timely delivery of orders. The superiority of Warung Bakso BRI in marketing is product quality, but Warung Bakso BRI must improve its employee politeness strategy